Interlanguage Development in Spoken English: Grammatical Errors among Indonesian EFL Learners - Kaharuddin Kaharuddin (Educia Journal, 2026)
Grammatical accuracy remains a persistent challenge for English as a Foreign Language (EFL) learners, particularly in spontaneous oral communication where learners must balance fluency and linguistic accuracy. This study investigated the grammatical errors produced by intermediate Indonesian EFL learners in spoken English and examined the underlying sources of these errors from the perspective of Second Language Acquisition (SLA). A descriptive qualitative design with quantitative support was employed. The participants were 21 intermediate students enrolled in an English Education program. Data were collected through picture description tasks and follow-up interviews, then analyzed using Corder’s error analysis framework, which classifies errors into omission, addition, selection, and misordering. The findings revealed 320 grammatical errors. Omission was the most frequent error category (49.6%), followed by selection (26.3%), addition (22.2%), and misordering (1.9%). Verb tense errors accounted for the highest proportion (33.8%), followed by errors involving articles, prepositions, subject–verb agreement, and noun endings. The analysis indicates that these errors primarily resulted from crosslinguistic influence, overgeneralization, insufficient grammatical knowledge, and incomplete rule application. The findings support contemporary SLA perspectives that learner errors represent developmental stages of interlanguage. Pedagogically, the study highlights the importance of integrating explicit grammar instruction with communicative speaking activities and timely corrective feedback to enhance learners’ grammatical accuracy and oral proficiency.